Leveraging Big Data to Advance Gender Equality - Rana, Ahmed Nauraiz (International Finance Corporation, Washington, DC, 2020)
Gender equality and the empowerment of women and girls, one of the Sustainable Development Goals, is a highly complex and challenging undertaking. We must address multiple issues, discrimination, violence, education, employment, economic resources, and technology, and work across economic sectors, from agriculture to financial services. Achieving gender equality will require significant amounts of accurate data about the situations and struggles of women and girls. Globally, however, there is a major gap in data that is disaggregated by sex, and this gap often renders women’s societal, cultural, and economic contributions and obstacles practically invisible. It can also exacerbate existing gender divides, feeding and reinforcing biases in social programs, access to financial and other services, economic opportunities, and even development programs designed to address gender inequality. Part of the solution may be in the form of big data, which, if used effectively, can provide the volume of data needed to portray women and their situations accurately, which in turn can inform the creation of evidence-based solutions.